When TAM is Unable to Build SMEs Passion to Rise Up During the Covid Pandemic - HITAYANI, Cokorda Putri; KUSUMA, I Gusti Agung Eka Teja; TAHU, Gregorius Paulus; LAKSEMINI, Kadek Dewi Indah Sri (Journal of Tourism Economics and Policy, 2024)
Measuring the ability of Technology Acceptance Model (TAM) variable; perceived ease of use (PEOU) and perceived usefulness (PU) of digital media to stimulate the passion (P) of SMEs through creating satisfaction in utilizing digital technology. This type of research is quantitative, using a pre-existing measurement scale related to PU, PEOU, satisfaction (S), and passion (P). Involving a sample of SMEs during the Covid pandemic, using the PLS SEM model as an analysis tool. The results of this study indicate that two elements of TAM, namely PU and PEOU, are not significantly able to stimulate SMEs passion. The success of TAM to stimulate passion is determined by its ability to create satisfaction in using digital media. Satisfaction has played a significant role as a full mediation on the influence of PU and PEOU on SMEs passion to use digital media. Apparently, SMEs passion to use digital media is largely determined by the evidence or tangible results that satisfy them. If digital technology has not been proven to provide satisfaction, it is difficult for SMEs to accept digital media to market their products. This research offers new insights, filling gaps in studies measuring TAM's ability in creating passion. Previously it has not been adequately explored.